Improving the Science Learning Outcomes of Grade V Students of SDN Rawaapu 06 Patimuan through the STAD Learning Model Assisted by Google Form - Ernasari Sri Asih Wulandari; Ristiana Dyah Purwandari (Proceedings Series on Social Sciences & Humanities, 2025)
This classroom action research aims to improve the learning process and learning outcomes of Natural and Social Sciences (IPAS) subjects by implementing the Student Teams Achievement Division (STAD) cooperative learning model supported by Google Form for fifth grade students of SDN Rawaapu 06, Patimuan District, Cilacap Regency in the 2024/2025 Academic Year. Based on the results of observations, the low IPAS learning outcomes were caused by the lack of variation in the application of learning models that could activate students and limited innovation in assessment. This research was conducted in three cycles, each of which consisted of stages of planning, action implementation, observation, and reflection. The subjects of this study were 23 fifth grade students of SDN Rawaapu 06. Data were obtained through Google Form- based learning outcome tests , student activity observation sheets, and field notes. The results of the study showed an increase in the average value of students' social sciences, which was originally 40.86 in the pre-cycle, to 51.73 in cycle I, 70.43 in cycle II, and 81.30 in cycle III. The percentage of students' learning completion also increased, namely from 13.04% in the pre-cycle to 30.43% in cycle I, 65.22% in cycle II, and 91.30% in cycle III. The application of the STAD model assisted by Google Form has proven effective in improving students' social science learning outcomes, strengthening active involvement in group discussions, and providing direct feedback that accelerates the process of analyzing evaluation results, especially on ecosystem material. This study recommends the use of the STAD model assisted by digital technology as an innovative alternative in social science learning at the elementary school level.